Rapid and sensitive detection of enrofloxacin hydrochloride based on surface enhanced Raman scattering-active flexible membrane assemblies of Ag nanoparticles. (1st November 2019) - Li, Hongji; Wang, Mingchao; Shen, Xiaoxue; Liu, Sui; Wang, Yan; Li, Yue; Wang, Qingwei; Che, Guangbo
Abstract: The abuse of antibiotics resulted in the pollution of river is more and more serious and it was necessary to exploit a sensitive detection method to improve the traditional analysis measurement. In this test, it is reported an Ag-based SERS sensing membrane synthesized by the technique of SERS detection and membrane separation. SERS analysis technique presented sensitive detection property, which could be applied into trace analysis. Membrane separation could effectively enrich the analytes to improve the sensitivity. The SERS membrane was synthesized by filtrating Ag nanoparticles (NPs) on the surface and investigating the amount of PVP and Ag NPs to the sensitivity. Meanwhile, the addition of Ag NPs effectively improved the hydrophilia to promote the detection effectivity in the water. By the investigations of optical analysis, the SERS membrane presented high sensitivity in the detection of antibiotics. Under the optimal condition, the SERS intensity presented good linear relationship with the concentration of antibiotics between 1.0 nmol L −1 and 200 nmol L −1 . This method provided a sensitive detection approach and broadened the investigation field of antibiotics detection. Graphical abstract: The preparation process had been exhibited in Scheme 1, this study focused on preparing Ag-based SERS analysis system for the detection of enrofloxacin hydrochloride (EH) on the PVDF membrane. Briefly, the PVDF membrane was synthesized by the method of non-solvent induced phase separation (NIPS) and fabricated with amount of Ag NPs by suction filtration to prepare the APM. Moreover, in order to enhance the sensitivity and increase the number of "hot spots", citric acid was selected to regulate morphology of Ag NPs with flower-like. The APM as a kind of flexible materials could more effectively be applied into detection vessels and avoid the waste caused by the centrifugation. This test provided a novel direction of SERS investigation.Image 1 Highlights: The technique mentioned can avoid the waste caused by the traditional centrifugation. The surface and amount of Ag nanoparticles were adjusted to improve the sensitivity of the SERS detection. This method carried out a method which ensured detection sensitivity and observably reduced the detection time.